A engenharia da história: natureza, geografia e historiografia na Amazônia - MORAES, Tarcisio Cardoso (Universidade Federal do Pará, 2014)
Of the end of century XIX even during the first decades of century XX, the engineers had been between the main names of the production of the historiography “pareanse”. This description has as objective to examine the conformation of a historiography tradition marked by the narrow dialogue with the geographic thought. The proximity between history and geography was articulated in such a way about of a perception dated regarding the social function that fit to each one of them, how about of a project politician thought for the “Amazônia”. In search to redefine, now under the republican look, the bases of the regional identity, it fit to history to review and to recover the Amazonian past inserting the region in a long tradition marked for the gradual development of the civilization. Already to geography it fulfilled to establish the bases of the necessary space knowledge to the identity local, and basic to the action of the State. I have as object the engineers João de Palma Muniz, Enrique Santa Rosa and Ignácio Baptista de Moura. Between historiography production, celebrations of civic events and the foundation of institutions, the project politician of these three engineers was part of a ampler movement of the “paraense” intellectuality. In other words, the engineer-historians had been special part of an ample exercise of understanding of the construction of the identity of the Amazon region from the optics of the power of the State-Nation.